BLOKELİ KUYRUK AĞLARININ ÇIKTI HIZI ANALİZİ. - HASKÖSE, Ahmet (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2020)
Queueing theory has been widely used in modelling and analysis of real-life stochastics systems. Today, most real-life systems such as manufacturing, communication and computer systems are represented and modeled by multistage queuing systems called queuing networks. Throughput is the number of products processed in a system per unit time, and is one of the key performance indicators in the analysis of stochastic systems. This study aims to investigate the effect of the configuration of queuing network and buffer capacities of queues on throughput of the system which have an important role in design and planning of a system. For this purpose, three different queue capacities of 5, 10 and 15 units in three different queue network configurations namely tandem, split-merge and arbitrary are examined for throughput analysis of queuing networks with blocking. It is seen that the throughput is affected by the queue network configuration and queue capacities. However, the experimental results suggest that throughput is the more sensitive to the configuration of queueing network.